Tryptophan Metabolism and Birth Asphyxia: What Implications for Neurodevelopment? - Galipo, Olivia; Scucces, Luisa; Morganti-Kossmann, Maria Cristina; Musumeci, Salvatore (Archives of Community Medicine and Public Health, 2024)
In children, perinatal asphyxia remains a frequent cause of disability and death. Increased catabolism of tryptophan through the kynurenine pathway, occurs in the human brain and systemic tissues alongside immune activation. The aim of this study was to determine the interaction between changes in the tryptophan pathway as well as cerebral and systemic inflammation triggered in asphyxic neonates and correlate these molecular changes with clinical parameters of asphyxia. The levels of the tryptophan catabolites, kynurenine, and quinolinic acid, as well as cytokines, were quantified in CSF and plasma of asphyxic neonates at 0 and 7 days after birth. Since macrophages and microglial cells are the source of quinolinic acid, we also measured chitotriosidase activity, which is a marker for monocytic activation. Significantly higher concentrations of IL-4, IL-6, IL-8, and IL-10 and a non-significant increase of TNF, and IFN-γ were found in CSF of asphyxiated infants at day 1 compared to day 7. Most of the inflammatory parameters normalized at 7 days, but chitotriosidase activity remained elevated. The children were followed up for an average of a 4-5 years period, and only in one case, the evaluation of general movements showed an absent fidgety.